Edukacja dziewcząt pod zaborem pruskim na przełomie XVIII i XIX wieku - Łukasiewicz, Dariusz (Biuletyn Historii Wychowania, 2014)
At the turn of 18th and 19th century the education of women on Polish territory underwent a gradual enlargement. Already in the period of the reforms of the National Education Commission, more girls received education; after the seizure of Greater Poland (Wielkopolska) by Prussia in 1793, Germany implemented their educational system, that meant the acceleration of development. Compulsory schooling in Prussian was introduced in 1794, however, it was still poorly enforced. In Prussia girls often attended lower school due to the requirement for a Protestant to have the ability to read the Scriptures. More and more often, they also attended secondary schools with syllabuses not extensively devoted to Latin, but to more practical skills, connected with so-called woman’s work, and to religious education. In Wielkopolska, lower education, private schools for girls and schooling by tutors in convents and midwifery schools increased significantly. Nevertheless, girls did not attend ordinary secondary schools, which retained an emphasis on teaching Latin, or colleges.